Frequently Asked Questions about Evapotranspiration (ET) Irrigation Controllers - Paul Monaghan; Ondine Wells; Michael Dukes; Maria Morera; Laura A. Warner (EDIS)
Evapotranspiration is the amount of water that is released into the atmosphere through evaporation and plant transpiration. An evapotranspiration irrigation controller is a device that uses data about the landscape, the type of irrigation system, and local weather conditions to determine when and how much to irrigate. This 5-page fact sheet explains how the technology functions as well as how to install, program, operate, and maintain an ET controller for a money- and water-wise sustainable home landscape that’s lush and beautiful. Written by Paul Monaghan, Ondine Wells, Michael Dukes, Maria Morera, and Laura Warner, and published by the Department of Agricultural Education and Communications, November 2015.